A comprehensive review on coating techniques to suppress the dendrites issue and improve the performance of lithium-ion batteries - Ali, Wajid; Ko, Ki Woong; Ahmed, Faheem; Lim, Jong Hwan; Choi, Kyung Hyun (JCT research, 2025)
In the realm of energy storage systems, lithium-ion batteries (LIBs) have solidified their dominant role due to their high energy density, long cycle life, and excellent efficiency. As a powerhouse for an array of applications including electric vehicles, portable electronics, and grid storage, the optimization of LIBs is a subject of robust and ongoing scientific inquiry. One of the critical challenges faced in LIBs is the formation of lithium dendrites—a type of crystal that grows on the lithium anode during the charging process. These dendritic structures can pierce the battery's separator, leading to a short circuit, and in worst-case scenarios, fires, or explosions. A promising avenue toward this goal lies in the development and application of innovative coating techniques. These processes can provide a protective layer on the anode, curtailing the growth of dendrites, and thereby enhancing battery life and stability. Thus, this review summarizes the various coating techniques which include physical vapor deposition, atomic layer deposition, and electrochemical deposition. This comprehensive review will delve into the varied coating techniques that have been proposed and implemented to address the dendrite problem. By investigating and comparing these strategies in depth, this article aims to provide a holistic understanding of current mitigation methods and a glimpse into the future trajectory of lithium-ion battery research. The hope is that this will inspire further exploration and innovation in the pursuit of ever more efficient and safe energy storage solutions.